Tanning addiction: conceptualization, assessment and correlates3. (4th July 2018) - Andreassen, C.S.; Pallesen, S.; Torsheim, T.; Demetrovics, Z.; Griffiths, M.D.
Summary: Background: Research into problematic tanning (or 'tanning addiction') has markedly increased over the past few years. Although several instruments exist to measure excessive tanning, most of these are psychometrically poor, are not theoretically anchored, and have been used mainly on small samples. Objectives: To develop a new tanning addiction scale based on a specific theoretical approach utilizing core addiction criteria. Methods: A scale comprising seven items (salience/craving, tolerance, mood modification, relapse/loss of control, withdrawal, conflict and problems) was administered online to a cross‐sectional convenience sample of 23 537 adults (mean ± SD age 35·8 ± 13·3 years). There was also assessment of demographic factors, the five‐factor model of personality, and symptoms of obsessive–compulsive disorder, anxiety and depression. Results: A confirmatory factor analysis showed that a one‐factor model gave an optimal fit with the data collected [root mean square error of approximation = 0·050, 90% confidence interval (CI) 0·047–0·053; comparative fit index = 0·99; Tucker–Lewis index = 0·99]. High factor loadings (0·78–0·91, all P < 0·001) and coefficient omega indicator of reliability (ω = 0·94, 95% CI 0·94–0·94) were also found using the new scale. In a multiple linear regression analysis, tanning addiction was positively associated with being female, not being in a relationship, extraversion, neuroticism, anxiety and obsessive–compulsiveness. It was also found that educational level, intellect/openness and depression were inversely associated with tanning addiction. Conclusions: The new scale, the Bergen Tanning Addiction Scale (BTAS), showed good psychometric properties, and is the first scale to conceptualize tanning addiciton fully within a contemporary addiction framework. Given this, the BTAS may potentially assist future clinical practice in providing appropriate patient care, prevention and disease management. Abstract : What's already known about this topic? A number of recent studies suggest that tanning has the potential to be addictive. What does this study add? This study describes a new brief screening tool for assessing tanning addiction based on contemporary addiction theory and core addiction criteria. What are the clinical implications of this work? Use of the scale can facilitate treatment and help to estimate the prevalence of tanning addiction in general populations worldwide. Linked Comment: Böhnke. Br J Dermatol 2018;179 :244–245 . Plain language summary available online Respond to this article